(untitled) (KYAMC Journal, 2022)
Background: Breast carcinoma is a heterogenous disease that represent a major health problem in Bangladeshi population. Several molecular markers have been detected over the past several decades, that are important in clinical aspects of breast carcinoma. Most recently, Vascular Endothelial Growth Factor (VEGF) is emerging as a prognostic marker in patients with several types of carcinoma including breast carcinoma. Many anti-angiogenic therapies targeting VEGF has been proven effective in many carcinomas. Objectives:This study was aimed to determine the expression of VEGF in different histomorphological types of breast carcinoma in an attempt to clarify its potential clinical outcome. Materials and Methods: This study was conducted in the Department of Pathology, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka from March 2018 to January 2020. In this study, 45 diagnosed cases of breast carcinoma were enrolled. Histopathological slides of all cases were re-evaluated. Thin sections were taken on coated slides from each paraffin block and immunohistochemical staining was done with VEGF antibody. Results: Among 45 cases, 73.3% cases were invasive ductal carcinoma and 13.3% cases were invasive lobular carcinoma. The immunohistochemical expression of VEGF was positive in 60% cases. In this study, 100% cases of in-situ ductal carcinoma, 83.3% cases of invasive lobular carcinoma and 57.6% cases of invasive ductal carcinoma showed overexpression of VEGF. However VEGF expression did not show significant association with histomorphological types. Conclusion: VEGF expression was found in 60% of breast carcinoma cases. It may serve as a potential therapeutic target for the management of breast carcinoma. KYAMC Journal Vol. 13, No. 01, April 2022: 9-12